Improving Image Classification Results by Applying Discrete Cosine Transform to Face Images - Şener, Abdullah; Ergen, Burhan (Bursa Uludağ Üniversitesi, 2022)
Today, the development of technology enables the rapid development of artificial intelligence studies. One of the most popular topics among the developing artificial intelligence studies is the creation and use of realistic false faces in virtual environments. In the study, a series of studies were conducted to distinguish between false and real faces based on images containing false and real faces. In the study, two different classification models (VGG, Xception) and three different methods (normal image, Fourier transform image, discrete cosine transform image) were applied to images and separate classification processes were performed. The obtained results were compared and provided to the researchers as a resource.

Günümüzde teknolojinin gelişmesi yapay zekâ çalışmalarının da hızlı bir şekilde gelişmesine olarak sağlamaktadır. Gelişen yapay zekâ çalışmaları arasında son zamanlarda popülerliği yüksek olan konulardan birisi sanal ortamlarda gerçekçi sahte yüzlerin oluşturulması ve kullanılmasıdır. Yapılan çalışmada içerisinde sahte ve gerçek yüzlerin yer aldığı görüntüler kullanılarak yüzlerin sahte/gerçek olduğunu ayırt etmek için bir dizi çalışmalar yapılmıştır. Yapılan çalışmada iki farklı sınıflandırma modeli (VGG, Xception) ve görüntüler üzerinde üç faklı yöntem (normal görüntü, Fourier dönüşümlü görüntü, Ayrık Kosinüs dönüşümlü görüntü) uygulanarak ayrı ayrı sınıflandırma işlemleri gerçekleştirilmiştir. Elde edilen sonuçlar karşılaştırılarak araştırmacılara kaynak olarak sunulmuştur.
YÜZ GÖRÜNTÜLERİNE AYRIK KOSİNÜS DÖNÜŞÜMÜ UYGULANARAK GÖRÜNTÜ SINIFLANDIRMA SONUÇLARININ İYİLEŞTİRİLMESİ
Keywords: Artificial Intelligence; Yapay Zeka